Using Surgical Microscope for Sclera Buckling and Transscleral Cryopexy: An Alternative Procedure of Treatment for Rhegmatogenous Retinal Detachment. (26th March 2014) - Zhong, Liu-xue-ying; Du, Yi; Liu, Wen; Huang, Su-Ying; Zhang, Shao-chong
Abstract : Purpose. To observe the long-term effectiveness of scleral buckling and transscleral cryopexy conducted under a surgical microscope in the treatment of uncomplicated rhegmatogenous retinal detachment. Methods. This was a retrospective analysis in a total of 227 consecutive patients (244 eyes) with uncomplicated rhegmatogenous retinal detachment (proliferative vitreoretinopathy ≤ C2). All patients underwent scleral buckling and transscleral cryopexy under a surgical microscope without using a binocular indirect ophthalmoscope or a contact lens. Results. After initial surgery, complete retinal reattachment was achieved in 226 eyes (92.6%), and retinal redetachment developed in 18 eyes (7.4%). The causes of retinal redetachment included presence of new breaks in eight eyes (44%), failure to completely seal the breaks in five eyes (28%), missed retinal breaks in four eyes (22%), and iatrogenic retinal breaks in one eye (6%). Scleral buckling surgery was performed again in 12 eyes (66%). Four eyes (22%) developed proliferative vitreoretinopathy and then were treated by vitrectomy. The sealing of retinal breaks and complete retinal reattachment were achieved in 241 eyes (98.8%). Conclusion. Probably because of clear visualization of retinal breaks and being controllable under a surgical microscope, the microsurgery of scleral buckling and transscleral cryopexy for uncomplicated retinal detachment exhibits advisable effectiveness.